Labilibaculum manganireducens gen. nov., sp. nov. and Labilibaculum filiforme sp. nov., Novel Bacteroidetes Isolated from Subsurface Sediments of the Baltic Sea - Vandieken, Verona; Marshall, Ian P. G.; Niemann, Helge; Engelen, Bert; Cypionka, Heribert (Frontiers in Microbiology, 2018)
Microbial communities in deep subsurface sediments are challenged by the decrease in amount and quality of organic substrates with depth. In sediments of the Baltic Sea, they might additionally have to cope with an increase in salinity from ions that have diffused downward from the overlying water during the last 9000 years. Here, we report the isolation and characterization of four novel bacteria of the Bacteroidetes from depths of 14-52 meters below seafloor (mbsf) of Baltic Sea sediments sampled during International Ocean Discovery Program (IODP) Expedition 347. Based on physiological, chemotaxonomic and genotypic characterization, it is proposed that the four strains represent two new species within a new genus in the family Marinifilaceae, with the proposed names Labilibaculum manganireducens gen. nov., sp. nov. (type strain 59.10-2MT) and Labilibaculum filiforme sp. nov. (type strains 59.16BT) with additional strains of this species (59.10-1M and 60.6M). The draft genomes of the two type strains had sizes of 5.2 and 5.3 Mb and reflected the major physiological capabilities. The strains showed gliding motility, were psychrotolerant, neutrophilic and halotolerant. Growth by fermentation of mono- and disaccharides as well as pyruvate, lactate and glycerol was observed. During glucose fermentation, small amounts of electron equivalents were transferred to Fe(III) by all strains, while one of the strains also reduced Mn(IV). Thereby, the four strains broaden the phylogenetic range of prokaryotes known to reduce metals to the group of Bacteroidetes. Halotolerance and metal reduction might both be beneficial for survival in deep subsurface sediments of the Baltic Sea.